How to facilitate seamless translation from basic concepts to new heart failure drugs. A scientific statement of the Heart Failure Association of the ESC - Tocchetti, Carlo Gabriele; González, Arantxa; Backs, Johannes; Pollesello, Piero; Rainer, Peter P.; Schiattarella, Gabriele Giacomo; Bellin, Milena; Begley, Glenn; Bock Marquette, Ildiko; Balligand, Jean-Luc; Falcao-Pires, Ines; Gorczynski, Rick; et al. (European journal of heart failure, 2025)
A rift has opened and is widening between basic research (bench) and clinical research and patients (bed) who need their new treatments, diagnostics and preventive strategies. This problem involving the ‘translation’ of basic scientific findings into clinical applications and potential treatments or biomarkers for a condition like heart failure is widely recognized both in academia and industry. Despite the attempts that have been made by both sides to improve this situation, the high attrition rates of drug development and the problem with reproducibility and translatability of preclinical findings to human applications still persist. As a result, the return on investment of basic research has been limited in terms of clinical impact. In this scientific statement we describe and discuss various issues with relevance to this theme and try to dissect how to move our field towards the development of more effective heart failure drugs. We zoom in on facilitating the process of heart failure drug development, the unnecessary gaps (‘valley of death’) between the critical steps in heart failure drug development, validation and de-validation of new concepts as early as possible (‘rigorous translation’). We describe forums on how to stimulate cross-talk and interaction between clinician-scientists, basic heart failure researchers, biotech and industry, and how to enable them to speak the same language, and lessons learned from successes outside the heart failure field.
Online veröffentlicht: 18. Juni 2025
Gesehen am 22.10.2025